Inovasi Sumber Daya Manusia: Menghadapi Perubahan dan Menyambut Kemajuan Teknologi Pada Sektor Perbankan Syariah (Studi PT. Kasus Bank Syariah Indonesia) - Effendi, Lutfiah; Hsb, Muthia Hafsari; Syafitri, Ade; Tambunan, Ria Tifanny; Suhairi, Suhairi (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
This research was conducted to find out the extent of preparation and readiness that has been carried out by Bank Syariah Indonesia as a whole to make efforts to improve the quality of superior services in the use of technological advances. Bank Syariah Indonesia was chosen as the subject of this study. The type of research carried out is using qualitative descriptive with the data used is secondary data taken from the observation process and literacy studies. From this research, it can be concluded that in facing changes and welcoming technological advances, Bank Syariah Indonesia itself has at least made several efforts such as conducting skill training for employees in digitalization and making efforts to improve the quality of human resources within the company to hone the ability and understanding of employees.